2012
DOI: 10.1111/j.1399-3046.2012.01670.x
|View full text |Cite
|
Sign up to set email alerts
|

Portal hypertension after combined liver and intestinal transplantation, a diagnostic and therapeutic challenge?

Abstract: 3 Abstract A widely accepted technique to transplant the liver-bowel bloc is first to perform a piggyback anastomosis of the donor suprahepatic vena cava to the recipient vena cava; second to restore the arterial blood supply through an aortic interposition graft; and third to insure venous drainage of the native foregut. The venous drainage of the native foregut can be restored through an end-to-end portocaval anastomosis between the donor infrahepatic vena cava and the recipient portal vein.Stenosis of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Gondolesi et al ( 4 ) suggested a modification of the conventional technique to an end-to-end anastomosis of native portal vein and donor IVC to mitigate the risks of development of varices. However, despite the adaptation of the technique, there have been case reports of development of thrombosis within the portacaval shunt ( 5 ). The portacaval shunt post liver intestinal transplant may have higher propensity for thrombosis due to the following reasons: (1) the hyperdynamic circulation present pretransplant in children with intestinal failure liver disease and portal hypertension is changed to a “low flow” system as it only drains part of the stomach, jejunum, and spleen; (2) correction of coagulation with a new functioning liver; and (3) presence of a procoagulant environment in immediate post-transplant period ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gondolesi et al ( 4 ) suggested a modification of the conventional technique to an end-to-end anastomosis of native portal vein and donor IVC to mitigate the risks of development of varices. However, despite the adaptation of the technique, there have been case reports of development of thrombosis within the portacaval shunt ( 5 ). The portacaval shunt post liver intestinal transplant may have higher propensity for thrombosis due to the following reasons: (1) the hyperdynamic circulation present pretransplant in children with intestinal failure liver disease and portal hypertension is changed to a “low flow” system as it only drains part of the stomach, jejunum, and spleen; (2) correction of coagulation with a new functioning liver; and (3) presence of a procoagulant environment in immediate post-transplant period ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is scant literature on how to treat ectopic variceal bleeding in those who have undergone Itx. The 3 existing reports on portal hypertensive bleeding in the liver-Itx cohort utilized a balloon dilation of stenosed shunt ( 5 ), side-to-side distal splenorenal shunt after unsuccessful balloon dilation of the portacaval anastomosis ( 3 ), and an end-to-end anastomosis for portosystemic shunts rather than end to side, potentially creating higher flow ( 4 ). Anastomotic technique in the portacaval shunt of case 1 was end to side.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation